Archaeological Sites as Space for Modern Spiritual Practice - Leskovar, Jutta; Karl, Raimund (Cambridge Scholars Publishing, 2018)
Archaeological heritage can be disputed, especially where it is important to religions and their practitioners. While the destruction of archaeological sites in war - often due to religious fervour - is frequently making the headlines, apparently lesser disputes about local heritage sites go unreported. This book focuses on these lesser, but much more frequent, potential conflicts between archaeological heritage management and conservation on the one hand, and practitioners of religious beliefs who use archaeological heritage in their practice on the other. By exploring case studies from Austr.